Kemampuan Metakognitif Terhadap Kemampuan Pemecahan Masalah Matematika SMP Kelas VIII - Indriyani, Pipit (Zona Education Indonesia, 2025)
The purpose of this research is to analyze the Influence of Problem Solving Ability Mathematics of VIII class student in SMP N 249 Jakarta. With metacognitive ability to solve mathematical problem. The research method used in this research is survey. Sampling technique using simple random sampling technique of 100 people. Instrument used is metacognitive ability questionnaire instrument and test instrument about math problem solving ability. To collect data on the research in the form of filling the questionnaire as much as 30 points statement with 5 alternative answers and test questions / description of 10 questions. Calculation Result The data normality test using Chikuadrat test obtained that both data are normally distributed. The analysis used simple regression and correlation. The result of hypothesis test resulted tcount > ttable that is 9,99> 1,984 ho rejected show that there is significant influence of metacognitive ability to solving problem of mathematics problem at SMP N 249 Jakarta on Alkanfactor Factorization Material.